Pengaruh Disiplin Kerja terhadap Produktivitas Aparatur Sipil Negara (ASN) di Lingkungan Distrik Sorong Kepulauan Kota Sorong - Yumame, Verdinanda; .Kastanya, James J; Pattiasina, Rendi Yudhistira (CV. Creative Tugu Pena, 2022)
Human Resources is one element of the organization, or work unit that is very important and has an important role in organizational activities. Internal problems of the organization, company or work device, one of which is the lack of discipline of existing employees, lack of facilities that support employee productivity and inadequate space. Likewise in the Sorong Islands District, as a regional apparatus organization engaged in government services, development and community development. The purpose of this study was to determine the effect of work discipline on the productivity of the State Civil Apparatus (ASN) in the Sorong District, Sorong Island Archipelago. Sampling was carried out using a population sample, that is, all of the population was involved to become a sample of 40 respondents. The type of research used is quantitative with simple linear regression analysis and T test. From the results of calculations using simple linear regression analysis, the regression equation is obtained as follows: Y = 17.432 + 0.505X. For the Work Discipline variable, a value of 0.505 is obtained which means that every time there is a change and an addition of one percent to the Work Discipline variable, the Productivity variable will increase by 0.505. Based on the analysis and discussion, it can be concluded that Work Discipline has a significant effect on Productivity in the Sorong District, Sorong Islands City. Keywords: Work Discipline, Productivity Human Resources, Human Resources